Differential cross sections for target excitation and positronium formation in positron-helium scattering - Chaudhuri, Puspitapallab [UNESP]; Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 1998)
Positronium formation and target excitation in positron-helium scattering have been investigated using the close-coupling approximation with realistic wave functions for the positronium and helium atoms. The following eight states have been used in the close-coupling scheme: [Formula Presented] [Formula Presented] [Formula Presented] [Formula Presented] [Formula Presented] [Formula Presented] [Formula Presented] and [Formula Presented] where Ps stands for the positronium atom. Calculations are reported of differential cross sections for elastic scatering, inelastic target excitation to [Formula Presented] and [Formula Presented] states, and rearrangement transition to [Formula Presented] [Formula Presented] and [Formula Presented] states for incident positron energies between 40 and 200 eV. The coincidence parameters for the transition to the [Formula Presented] state of helium are also reported and briefly discussed. © 1998 The American Physical Society.